2014
DOI: 10.1103/physrevd.90.124033
|View full text |Cite
|
Sign up to set email alerts
|

Possible observational windows for quantum effects from black holes

Abstract: Quantum information transfer necessary to reconcile black hole evaporation with quantum mechanics, while approximately preserving regular near-horizon geometry, can be simply parameterized in terms of couplings of the black hole internal state to quantum fields of the black hole atmosphere. The necessity of transferring sufficient information for unitarization sets the strengths of these couplings. Such couplings via the stress tensor offer apparently significant advantages, and behave like quantum fluctuation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 71 publications
(162 reference statements)
1
97
0
Order By: Relevance
“…Such "primordial black holes" may even contribute to the dark matter in the Universe (Blais et al, 2002) and produce gravitational waves (Bird et al, 2016). Second, according to recent speculations, quantum effects may potentially become relevant near the horizon of a macroscopic black hole; for example, in the form of a "firewall" (Calmet, 2015); see also Giddings (2014). It is an intriguing question whether such effects, if present, could be observed with the EHT.…”
Section: Black Holes and Quantum Theorymentioning
confidence: 99%
“…Such "primordial black holes" may even contribute to the dark matter in the Universe (Blais et al, 2002) and produce gravitational waves (Bird et al, 2016). Second, according to recent speculations, quantum effects may potentially become relevant near the horizon of a macroscopic black hole; for example, in the form of a "firewall" (Calmet, 2015); see also Giddings (2014). It is an intriguing question whether such effects, if present, could be observed with the EHT.…”
Section: Black Holes and Quantum Theorymentioning
confidence: 99%
“…Giddings, in particular, has observed that the possibility that such quantum gravity effects could lead to observable effects cannot be completely excluded, and listed a number of such possibilities in [14]. For instance, quantum gravitational fluctuations of the metric could disrupt the accretion flow in the near-horizon atmosphere region, distort or suppress the photon ring [16], or distort the edge of the shadow [17].…”
mentioning
confidence: 99%
“…Examples are the quantum description of black holes as Bose-Einstein condensates [4,5], fuzzbals [6], Planck star tunnelling [7][8][9][10][11][12][13], and Giddings's metric fluctuations [14]. Also, one possible interpretation of the firewall theorem [15], which has recently raised a lively discussion in the theoretical world, is as an indication that "something strange" should have to happen at the horizon of a macroscopic black hole, possibly violating the hypotheses of the theorem, which include the validity of local quantum field theory on a given background geometry.…”
mentioning
confidence: 99%
“…In the framework of standard physics, the spacetime geometry around these objects should be described by the Kerr solution of general relativity. However, an observational confirmation is still lacking and deviations from standard predictions can be motivated by a number of arguments, from classical extensions of general relativity [2][3][4][5] to macroscopic quantum effects [6][7][8].…”
Section: Introductionmentioning
confidence: 99%